2019
DOI: 10.1186/s12885-019-5812-0
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic assessment of breast carcinoma submitted to neoadjuvant chemotherapy with pathological non-complete response

Abstract: Background Breast cancer with pathological non-complete response (non-pCR) after neoadjuvant chemotherapy (NAC) has a worse prognosis. Despite Neo-Bioscore has been validated as an independent prognostic model for breast cancer submitted to NAC, non-pCR carcinoma was not assessed in this setting. Methods This is a retrospective trial that included women with localized breast cancer who underwent NAC and had non-pCR carcinoma in surgical specimen between 01/01/2013 to 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…In our study the post-menopausal group and those aged above 51 had a better clinical response ( P <0.05) than those who were pre-menopausal and those aged below 50 years. Resende et al 23 shows no relationship with menopausal state. Del Prete et al 21 showed good pathological response in premenopausal patients.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In our study the post-menopausal group and those aged above 51 had a better clinical response ( P <0.05) than those who were pre-menopausal and those aged below 50 years. Resende et al 23 shows no relationship with menopausal state. Del Prete et al 21 showed good pathological response in premenopausal patients.…”
Section: Discussionmentioning
confidence: 93%
“…In Miglietta et al, 22 a good response was seen with Her2-neu over-expressed tumors. Resende et al 23 showed no relationship with HER2–neu status of the patients. In our study the post-menopausal group and those aged above 51 had a better clinical response ( P <0.05) than those who were pre-menopausal and those aged below 50 years.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Then, we further investigated the impact of LDN in the response to standard treatment, especially in non-metastatic BC patients selected for neoadjuvant chemotherapy (NACT), since a poor response to this treatment is a predictive factor for recurrence and disease progression (18,19). NACT is the treatment of choice for BC patients with tumors larger than 2 cm and/or with disease extension to axillary lymph nodes, or with inflammatory and inoperable tumors, independently on the BC subtype.…”
Section: Resultsmentioning
confidence: 99%
“…However, subgroup analysis revealed that the survival rates of patients who did not achieve pCR were lower compared with those of patients who achieved pCR, even when compared with the adjuvant chemotherapy group ( 7 9 ). This may be due to the increased risk of recurrence caused by residual lesions in patients who received NAC but did not achieve pCR ( 10 ). TNBC is a heterogeneous disease, which comprises subtypes with different biological behaviors and clinical outcomes ( 11 ).…”
Section: Introductionmentioning
confidence: 99%